Cu and Zn adsorption in an Oxisol treated with pig slurry Adsorção de Cu e Zn num Latossolo Vermelho tratado com dejetos suínos - Lopes C.* (2014)
Cooper and zinc derived from pig slurry can accumulate in the soil, posing risks to human and animal health. The objective of this study was to determine the adsorption capacity and the competition of Cu and Zn in Oxisols that received continued applications of 200 m3ha-1year-1of pig slurry for seven years and to compare with soil under natural conditions. To evaluate the adsorption, Cu and Zn solutions were applied to the soil at concentrations of 0, 25, 50, 100, 150, 200, 400, 1.200 μmol L-1; soil:solution ratio of 1:100.Merck Certipur standard solution 1.000 mg L-1 was utilized to construct the levels of Zn and Cu. The adsorption of Cu showed a sigmoid behavior (S-type isotherm) in soil with no slurry application and linear behavior (C-type isotherm) in soil with pig slurry. The maximum adsorption of Cu in soil without pig slurry was 3,021 mg kg-1. For Zn, all the isotherms showed linear behavior. The maximum adsorption capacity of Cu and Zn was not reached in soil with slurry. These results show that the studied Oxisol has a high capacity to retain Zn and Cu from pig slurry.